1993
DOI: 10.1016/0741-5214(93)90258-n
|View full text |Cite
|
Sign up to set email alerts
|

Saphenous vein biopsy: A predictor of vein graft failure

Abstract: We conclude that GSVs with thick and calcified walls or hypercellular intima at the time of grafting are at increased risk of developing intragraft lesions that may lead to graft failure. Frequent duplex ultrasonography surveillance is particularly warranted for such high-risk grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
36
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 9 publications
3
36
1
Order By: Relevance
“…Finally, Aaltomaa et al (26) showed that SV endothelial cells of diabetic patients have a greater tendency to proliferate compared with those cells harvested from normal subjects, suggesting an abnormal intrinsic regulation of endothelial functions. These findings suggest that diabetes may exacerbate the postoperative maladaptive changes of venous conduits (27,28). Diabetes, however, does not invariably alter vascular integrity, particularly at the venous district.…”
Section: Discussionmentioning
confidence: 78%
“…Finally, Aaltomaa et al (26) showed that SV endothelial cells of diabetic patients have a greater tendency to proliferate compared with those cells harvested from normal subjects, suggesting an abnormal intrinsic regulation of endothelial functions. These findings suggest that diabetes may exacerbate the postoperative maladaptive changes of venous conduits (27,28). Diabetes, however, does not invariably alter vascular integrity, particularly at the venous district.…”
Section: Discussionmentioning
confidence: 78%
“…Neither better preoperative patient selection nor improved intraoperative handling of vascular conduits has been sufficient to eliminate the disparity between SVGs and AGs. 2,3 Recent studies have increasingly focused on biological differences between venous and arterial conduits that may affect their response to surgery. 4,5 In addition to structural differences (eg, less-developed elastic tissues), the cellular composition of veins is dissimilar to that of arteries.…”
mentioning
confidence: 99%
“…4 Pathology studies have shown that differences in the wall thickness of grafts are predominantly caused by differences in thickness of the intima, rather than of the media or adventitia. 5 As most patients in this study had stable or reduced wall thickness between postoperative months 1 and 12, it is likely that wall thickening is most active within the first 4 to 6 weeks after SVG implantation. We postulate that early cellular and extracellular changes mediate increased wall thickness of the first 6 weeks, which then plateaus and, in the absence of atherosclerosis, may regress.…”
Section: Discussionmentioning
confidence: 99%
“…3 Venous conduits may exhibit mild intimal or medial fibrosis pre-grafting, but most develop further intimal thickening within 4 to 6 weeks of arterial anastomosis. In angiographically normal SVG, intravascular ultrasound (IVUS) and pathological studies have shown a doubling of intimal thickness 4 and total wall thickness 5 by the end of the first postoperative year.…”
mentioning
confidence: 99%